Implementation of New Prudential Banking Principles Through 6c + 1s at BSI KCP Godean Yogyakarta - Wibisana, Karin Maria; Febriyanti, Novi (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
The purpose of this research is to find out the application of new prudential banking principles through 6c + 1s at BSI KCP Godean Yogyakarta and to find out the obstacles and solutions carried out by BSI KCP Godean Yogyakarta in implementing prudential banking principles through 6c + 1s. This study used a qualitative research method with field research. The results of the study found that Bank BSI KCP Godean in providing musyarakah financing to prospective customers has applied the precautionary principle by using the 6c + 1s principle. It's just that there is one indicator in the capacity principle that has not been implemented, namely an indicator of an assessment through an educational approach or assessing the educational background of prospective customers. The obstacle in implementing new prudential banking through the 6c + 1 principles is that it is influenced by two factors, namely internal factors originating from the bank such as negligence or lack of thoroughness on the part of the bank in charge of surveying customers and external factors originating from the customer side which are caused due to two elements namely due to elements of intentionality and unintentionalness. The solution implemented by BSI KCP Godean Yogyakarta in overcoming these obstacles is by conducting routine training for employees, carrying out mutations, rotating employees, and mentoring and supervising superiors.